Erratum to “Charge-Based Compact Modeling of OECTs for Neuromorphic Applications” - Ghader Darbandy; Malte Koch; Lukas M. Bongartz; Karl Leo; Hans Kleemann; Alexander Kloes (IEEE Journal of the Electron Devices Society)
Presents corrections to the paper, (Erratum to “Charge-Based Compact Modeling of OECTs for Neuromorphic Applications”).